STRUKTUR KOMUNITAS GASTROPODA PADA HUTAN MANGROVE KEBUMEN JAWA TENGAH - Wintah wintah (Journal of Aceh Aquatic Sciences, 2018)
The Kebumen mangrove forest experienced a decline in ecological functions caused by the pollution of jellyfish processing waste around mangrove forests. Gastropods are biota associations of mangrove forests whose existence is influenced by environmental factors. This study aims to determine the community structure of gastropods in Mangrove Forest in Kebumen District. Sampling technique for mangrove and gastropod sampling. Gastropods found were 17 species, Ceritidhea alata, Ceritidhea quadrata, Telescopium telescopium, Neritina violacea, Neritina lineata, Neritina zigzag, Neritina albicilla, Neritina antiquata, Neritina turita, Vittina variegat, Cassidulla aurisfelis, Cassidulla nucleus, Littoraria carinifera, Assimenia bresvicula, Hastula sp, Pirenella cingulata, and Littoraria melanostoma. The highest density of gasropods are Ceritidhea alata and Neritina violacea. The pattern of distribution of majority gastropods is clustered.